Development of 3D Simulation Video in the Field of Computer Component Manufacturing - Ali, Azita; Mohamad Zinin, Mohamad Hanan (Research and Innovation in Technical and Vocational Education and Training, 2023)
This research was conducted to develop a manufacturing simulation video application to convey information related to computer component manufacturing using the Android application platform. In this field, namely computer manufacturing, there is still a shortage of technological resources that can be used as interesting and more interactive teaching aids. The development of this android application is very interesting and in line with current information delivery methods which can be translated into a more dynamic form than the use of statistically presented information delivery using the right distance to the smartphone screen. The ADDIE model serves as a guide during the development process of this application. The platforms used to develop this application are Unity, Blender, Adobe Illustrator CS6, Adobe Photoshop CS6, and Wonder Share Filmora. Testing and evaluation of this application is carried out through the expert survey method conducted on five experts. In this study, three interface experts were selected, and the lecturers involved had broad skills in creative multimedia. The results of the study indicate that all experts have provided positive comments, suggestions, and input on this developed application. In conclusion, with this product, the developers believe they can provide a better understanding of a process that occurs in the computer manufacturing sector. The success of this application development is expected to be an interactive manufacturing knowledge platform and able to achieve every goal that has been set by the developer.